COMBATING PIRACY: THE INDONESIAN CASE - Kamil Ariadno, Melda (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2013)
Piracy at sea has been a threat to international navigation ever since the sea traverse by ships from west to east and north to south. Threat to international trade has resulted to various efforts in combating piracy regionally as well as internationally. International law has differentiated between piracy and sea-armed robbery, while the first requires regional or international cooperation due to universal jurisdiction, the second will directly fall under the jurisdiction of coastal state. Strait of Malacca has been used by international navigation and very fragile to the threat of piracy or even appropriately called as sea armed robbery since most of the time happened in the part of Indonesian territorial sea. Various efforts to combat piracy have been carried out by Indonesia including to cooperate with Malaysia and Singapore. This article discuss about piracy at sea, its legal definition and effort to combat piracy.